Fundamental economic variables: A study from the leontief methodology - Everlam Elias Montibeler; Daniel Ribeiro de Oliveira; Daniel Rodrigues Cordeiro (EconomiA, 2018)
This paper aims to investigate the level of main "fundamental variables" of the Brazilian economy: rate of profit, surplus value, composition of capital, vertically integrated labor composition and productiveness. Using the national accounting system of 2009, Inverse Matrix of Leontief and Vertical Integration of Capital and Labor, by Pasinetti, the current investigation analyzes the level of competitiveness of Brazilian economy. The estimations cover a set of 53 productive sectors and it is designed to rank those sectors depending on their competitiveness. Final objective is to execute an analysis, from classical economic theory, that analyzes behavior between price and values, as well as, variation measurement and deviation.
Keywords: 330; Brazil; Fundamental variables; Input-output table; Leontief Inverse